1992
DOI: 10.1016/0014-5793(92)80718-v
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of nuclear proteins to DNA by cis‐diammminedichloroplatinum in intact cells Involvement of nuclear matrix proteins

Abstract: In order to detect the nuclear matrix proteins involved in DNA binding, avoiding possible artifacts derived from the disruption of nuclei. proteins were crosslinkcd to DNA by the action of cis-diammincdichloroplatinum on intact chicken liver cells and analyzed by twodimcnsional gel eleetrophoresis. At Icast eleven spccics ofcrosslinkcd proteins wcrc found to dcrivc from the nuclear matrix prepared from the same cell type, and live of these were found also among the proteins crosslinked to DNA in intact liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
2
22
0
Order By: Relevance
“…The observation that PDI co-isolates with the NM and crosslinks to DNA (data not shown) is consistent with earlier reports [Ferraro et al, 1992[Ferraro et al, , 1996 that an isoform of PDI, ERp60, is part of the internal NM. Herein, we show that the presence of 1 mM DTT, presumably through its affects on NM-associated proteins containing redox sensitive disulfide linkages, e.g., PDI, altered the anchoring of DNA loops such that the unwinding of supercoils was enhanced and the rewinding of them was inhibited.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observation that PDI co-isolates with the NM and crosslinks to DNA (data not shown) is consistent with earlier reports [Ferraro et al, 1992[Ferraro et al, , 1996 that an isoform of PDI, ERp60, is part of the internal NM. Herein, we show that the presence of 1 mM DTT, presumably through its affects on NM-associated proteins containing redox sensitive disulfide linkages, e.g., PDI, altered the anchoring of DNA loops such that the unwinding of supercoils was enhanced and the rewinding of them was inhibited.…”
Section: Discussionsupporting
confidence: 91%
“…This notion is consistent with the observation that heat-induced binding of proteins to the NM masks the DTT induced loosening of the DNA-NM anchor complex. Although the exact structure of the complex remains elusive, these results and those of others [Altieri et al, 1993;Ferraro et al, 1992Ferraro et al, , 1996, provide significant new insight into DNA-NM anchoring.…”
Section: Discussionmentioning
confidence: 86%
“…Wedrychowski et al [1986, 19891 and ourselves [Ferraro et al, 1992 have demonstrated that many proteins cross-linked in such a way in intact cells or nuclei derive from the nuclear matrix.…”
mentioning
confidence: 98%
“…Although cis-DDP can also produce proteinprotein cross-linking, an indirect bond mediated by unknown protein(s) seems unlikely in our in vivo cross-linking conditions [Banjar et al, 1985;Ferraro et al, 1992]. Moreover, some of the sequences found in the coimmunoprecipitated DNA were already shown to bind NM23/NPDK by in vitro EMSA experiments [Postel et al, 2000].…”
Section: Discussionmentioning
confidence: 94%
“…After 60 min of incubation at 378C, 1/200 volume of 1 M thiourea solution was added to stop the cross-linking reaction [Ferraro et al, 1992;Cervoni et al, 2003]. The cells were harvested by centrifugation at 2,000g for 5 min at 48C.…”
mentioning
confidence: 99%